ANALISIS KETIDAKSEIMBANGAN BEBAN PADA GARDU DISTRIBUSI KA 2085 DI PT. PLN (Persero) DISTRIBUSI BALI RAYON MENGWI BADUNG - Suputra, R.; Weking, A. I.; Rinas, W. (Jurnal SPEKTRUM; Vol 5 No 1 (2018): Jurnal SPEKTRUM, 2018)
The difference in the value of the current flowing in each phase conductor in a power distribution network, causes an unbalanced state. The unbalanced state of a power grid will result in an increase in power losses. This study is conducted by analyzing balanced state power losses and unbalanced state under peak load conditions at JTR and SR of K8585 distribution relay, unbalance burden on secondary distribution network KA 2085 has resulted in the loss of load-balanced power of peak load time of 0.104 kW with a loss-loss prosenase of 0.33%. While the losses for unbalanced load peak load time of 0.211 kW with a percentage loss of 0.69%.